Covid-19 Information on Social Media and Anxiety Disorders in Students - Sherina Pebriany Marpaung; Syifa Syarifah Alamiyah; Theressia Sunday Sillalahi (Universitas Islam Balitar, 2021)
The Covid-19 pandemic has had an impact on all levels of society around the world, including in Indonesia. Since its appearance in Wuhan China, various information and news about this virus has been massively broadcasted through various channels. Posts on social media can be in the form of news links from official mass media channels, in the form of opinions about Covid-19. This research focused on the relationship bertween information of covid-19 on social media and the level of anxiety of university students and the objective of this research to seek the relationship or causality among both variable. Independent variable on this research is the social media post about covid-19 (X), which is influence to dependent variable that is the level of anxiety of university students. A number of 100 students participated on the research and filled the questionnaire, which was distributed along September 2020. At that time, Indonesia has experienced the second wave of the Covid-19 global pandemy. The study find that there is relationship between Covid-19 information on social media and the anxiety level of university students. However the relationshipsamong both variables is on the low level. These findings show imply that there is a need for the party who are in the effort on pandemic mitigation to put attention about the information spread on the society, considering that those information could influence to the mental health of the university students and the welfare of the society at general